SEAD - The Strategic Environmental Archaeology Database - Buckland, Philip; Eriksson, Erik J; Viklund, Karin; Linderholm, Johan; Svensson, Patrik (Umeå University, 2011)
SEAD is an open access multiproxy environmental archaeology and palaeoecology database and software development project. The database contains the raw data from the scientific analysis of archaeological, Quaternary geological and related investigations, mainly from Sweden and Europe, but also to a lesser extent from outside of the EU. The raw data include counts of plant macrofossils, fossil insects and pollen along with geoarchaeological measurements and ceramic analyses. Dating methods stored range from calendar or coinage records, through radiocarbon (14C) and dendrochronology, to broad period definitions. SEAD is built around a flexible modular architecture and can be expanded to cope with any related material. Online/offline interfaces for data entry and extraction are available, including the advanced low level aggregation of data from multiple sites. The project is part of an international network of palaeoecology databases, and includes a large amount of modern reference, calibration and ecological data to aid interpretation.

Purpose:

The primary purposes of SEAD is the dissemination of scientific data from archaeological and palaeoenvironmental investigations. This includes the online publication of grey literature and its associated data (especially from the National Environmental Archaeology Lab in Umeå, Ceramics and Dendrochonology Labs in Lund) as well as databases previously not available online. SEAD also aims to provide powerful interrogation and analysis tools which allow users to identify trends and relationships through a multiple and broad range of datasets for looking at multi-scale environmental and climate change and human impact. SEAD also integrates modern ecology with the fossil data and provides a comprehensive bibliography, methods reference and site metadata.

SEAD är en fri multiproxy miljöarkeologi- och paleoekologidatabas samt programvaruutvecklingsprojekt. Databasen innehåller rådata från den vetenskapliga analysen av arkeologiska, kvartärgeologiska och associerade undersökningar. Dessa härstammar främst från Sverige och Europa, men också i mindre utsträckning utanför EU. Rådata som ingår inkluderar växtmakrofossildata, fossil insektersdata och pollenanalysresultat tillsammans med geofysiska mätningar och keramiska analyser. Dateringsmetoder från kalender eller mynt register, radiocarbon (14C) och dendrokronologi samt breda perioddefinitioner inräknas. SEAD är byggd kring en flexibel modulär arkitektur och kan utökas för att klara andra datatyper. Online/offline gränssnitt för in- och utmatning av data samt analys finns tillgängliga, inklusive avancerad aggregering av data från flera geografiskt disparata undersökningar. Projektet ingår i ett internationellt nätverk av paleoekologiska databaser, och innehåller en stor mängd moderna referens, kalibreringar och ekologiska data för att underlätta tolkning.

Syfte:

De främsta syftena med SEAD är spridning av vetenskapliga data från arkeologi- och palaeomiljöutredningar. Detta inkluderar publicering av grå litteratur och dess uppgifter (särskilt från de Nationalla Environmental Archaeology Lab i Umeå, Keramik och Dendrochonology laboratorierna i Lund) samt databaser tidigare inte tillgängliga online. SEAD syftar också till att ge kraftfulla analysverktyg som tillåter användare att identifiera trender och relationer i ett brett utbud av dataset för att titta på flerskalig miljö- och klimatförändringar och mänsklig påverkan. SEAD integrerar också moderna ekologi med fossila data och erbjuder omfattande bibliografi, referensmetoder och platsmetadata.
Strategisk miljöarkeologisk databas - SEAD
Keywords: ENVIRONMENTAL CHANGES; MILJÖFÖRÄNDRINGAR; CLIMATE CHANGE; KLIMATFÖRÄNDRINGAR; ceramics; keramik; subfossils; subfossiler; plant macrofossils; växtmakrofossiler; quaternary geology; kvartärgeologi; dating; datering; insects; insekter; dendrochronology; dendrokronologi; pollen; pollen; proxy data; proxydata; geoarchaeology; geoarkeologi; palaeoecology; paleoekologi; environmental archaeology; miljöarkeologi; HISTORY; HISTORIA; Geology; Geologi; Geochemistry; Geokemi; Other Earth Sciences; Annan geovetenskap; Ecology; Ekologi; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi